Sustainable Trekking in Nepal: Leave No Trace Practices. (SADGAMAYA, 2026)
Trekking business in Nepal spans the entire country across major areas (Everest, Annapurna, Langtang, Manaslu, Mustang, etc.) and is economically significant but also exerts tremendous pressure on vulnerable mountain environments. This article focuses on how the "Leave No Trace" (LNT) philosophy and its associated sustainability practices are being adopted along Nepal's trekking paths. Based on field-level studies (i.e., waste audits and local surveys) and policy documents, we examine environmental impacts (deforestation, climate risks, solid waste, and water pollution), stakeholder roles (trekkers, tour operators, park authorities, and locals), and challenges in place. Conservation area projects like ACAP and MCAP have spurred communities to pool tourism revenues and resources. Government and nongovernment efforts (e.g., SPCC in Khumbu) focus on waste-collection infrastructure. Yet a study finds that even well-touristed areas have poor waste management: e.g., Ghorepani (Annapurna) has waste bins but "no specific regulations to protect the environment," and consequently minimal environmental returns. We look at good practice (integrated waste management plans, porter cleanup, trekker education, environmentally friendly lodges) and evidence of loopholes in enforcement and knowledge. The review synthesizes literature from 2014 to 2024 (peer-reviewed articles, NGO/government reports) to assess the potential to enhance LNT in Nepali trekking.